Partisipasi Masyarakat dalam Pengelolaan DAS Bone, Provinsi Gorontalo - Pakaya, Parid; Sudarmanto Hasan; Suryadi Syamsudin; Fitryane Lihawa; Iswan Dunggio (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
Watershed management requires active community participation as a key actor in ensuring environmental sustainability. This study aims to analyze the forms, levels, and factors influencing community participation in the management of the Bone Bolango Watershed in Gorontalo Province. The method used is a descriptive qualitative approach supported by quantitative data from questionnaires distributed to 45 respondents. The results show that 75.6% of respondents are unaware of watershed programs, and only 24.4% have been involved in the planning stage. In the implementation stage, participation reaches 53.3%, mainly in reforestation and waste management activities. About 48.9% are aware of the evaluation process, but only 40% consider it transparent. Some community members (44.4%) perceive economic benefits, especially from planting productive trees. Educational activities are considered effective by 71.1% of respondents, although participation remains limited. The Bone Watershed Forum is viewed as strategic, yet community involvement needs to be strengthened. Enhancing local institutional capacity, transparency, and cross-sector collaboration is essential to improving sustainable community participation in watershed management.